EVALUASI EMPIRIS TERHADAP PERSEPSI PEMAKAI ATAS BENTUK LAPORAN AUDIT YANG BERUBAH - Dyah Setyorini (Universitas Negeri Yogyakarta, 2005)
This research aims to evaluate empirically on how the user’s perception of the changed of auditing report form (from NPA to SPAP) to increase user’s audited report conception and check or investigate expectation gap between auditor and audit report user (credit analyst) based on message communicated through auditing report. The user conception of auditing report will be observed in 16 dimensions which are: Auditor’s Independence, Auditor’s Judgement and Discretion, Decision Usefulness, Auditing Goals, Management’s Representation, Specific versus Whole, Performance Monitoring, Credibility, Auditor-Management Conflict, Accounting Standards, Viability of Company, and Proper Accounting Records. This expectation gap will be viewed from three factors which are Auditor’s Responsibility, Reliability of Audited Financial Statement, and Benefit of Audited Report in Decision Making. Based on research data collecting which was done by survey where some of data were sent by post and the others were given to respondent directly, it has reached as many as 38 independent auditors and 61 credits analyst. Data analysis was done by Mann-Whitney U test method. This research result explains that there are different perceptions between independent auditors and credit analyst related with the independent auditor’s responsibility and reliability of audit report, but both of groups have the same perceptions on the benefit of audit report. Related with the user perception on the change of auditing report form, it is showed that conception differences between credit analyst which is given standard audit report based on SPAP and credit analyst which is given standard audit report based on NPA only occur in three dimensions which are independence dimension, auditing goals dimension, and proper accounting record dimension. So, it can be outlined that the change of auditing report form (NPA to SPAP) does not produce conception change significantly on audit report user.